Field reports of Iowa birds contributed by Thomas H. Kent, November 27, 1987 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1987)
Fall report of birds and locations contributed by Thomas H. Kent, November 27, 1987. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed